Narrative inquiry in language teaching and learning research - Barkhuizen, Gary Patrick; Benson, Phil 1955-; Chik, Alice (New York Routledge, 2014)
"This text provides an entry-level introduction to narrative inquiry methods, grounded in empirical research within the fields of language teaching and learning. The book discusses basic concepts, explains how and why these methods have been used in language teaching and learning research, and outlines different approaches covered by this research. Narrative Inquiry in Language Teaching and Learning Research is a focused and practical guide for readers interested in understanding or carrying out narrative studies"--Provided by publisher.
Includes bibliographical references (pages 117-128) and index.
Keywords: Language and languages -- Study and teaching -- Research; Second language acquisition -- Research; Discourse analysis, Narrative; Linguistic analysis (Linguistics)